HUBUNGAN TINGKAT SOSIAL EKONOMI DAN BUDAYA DENGAN KEPATUHAN MENJALANI FISIOTERAPI PASIEN PASCA STROKE DI RSUD ARIFIN ACHMAD PROVINSI RIAU - Anggarawati, Wiwik Suryandartiwi; Firdaus , Muhammad; Yuliana, Anastasya Shinta; Bisra, Marido (Journal of Hospital Administration and Management (JHAM), 2024)
Adherence to physiotherapy is a crucial factor in the recovery process of post-stroke patients. Socioeconomic status and cultural factors are suspected to play a significant role in influencing patient adherence to therapy. This study aims to analyze the relationship between socioeconomic status and cultural factors with adherence to physiotherapy among post-stroke patients at RSUD Arifin Achmad, Riau Province. This study employs a quantitative cross-sectional design. The research sample consists of post-stroke patients undergoing physiotherapy at RSUD Arifin Achmad, selected using purposive sampling. Data were collected through questionnaires and patient medical records, then analyzed using correlation statistical tests to examine the relationship between socioeconomic status, cultural factors, and adherence to physiotherapy. The results indicate a significant relationship between socioeconomic status and patient adherence to physiotherapy (p < 0.05), where patients with higher socioeconomic status tend to adhere more to therapy schedules. Additionally, cultural factors, such as beliefs in traditional medicine and family support, also influence patient adherence. Therefore, a more holistic approach is needed in post-stroke rehabilitation programs, considering socioeconomic and cultural aspects to enhance patient adherence to physiotherapy.